A double‐edged sword: The moderating role of conscientiousness in the relationships between work stressors, psychological strain, and job performance. (12th September 2014) - Lin, Weipeng; Ma, Jingjing; Wang, Lei; Wang, Mo
Summary Although conscientiousness was commonly viewed as a type of personal resource to help individuals reduce strain or mitigate the impacts of stressors, empirical research demonstrated mixed results. Based on the personal resource allocation perspective, we posited that rather than functioning as personal resource per se, conscientiousness may act as a key factor influencing how individuals allocate their personal resources. The current study examined the moderating roles of conscientiousness in the relationships that work stressors (i.e., challenge stressors and hindrance stressors) have with employee psychological strain and job performance by using multi‐source, time‐lagged data collected from 250 employees working at two companies. The results showed that both challenge stressors and hindrance stressors were positively related to psychological strain. Conscientiousness moderated the relationships between both stressors and psychological strain, such that the positive relationships were stronger for individuals with high conscientiousness. Conscientiousness also moderated the relationship between challenge stressors and performance, such that the relationship was positive for individuals with high conscientiousness but negative for those with low conscientiousness. Altogether, the findings suggest that conscientiousness acts as a double‐edged sword that both promotes performance and exacerbates the stress reaction of employees when they are confronted with stressful situations. Copyright © 2014 John Wiley & Sons, Ltd.